TOCOTRIENOL-RICH FRACTION MODULATE THE PHOSPHOINOSITIDE 3-KINASES/AKT SIGNALING PATHWAY GENES AND PREVENT OXIDATIVE STRESS IN NICOTINE-INDUCED PRE-IMPLANTATION EMBRYOS - KAMSANI, NURUL HAMIRAH; AB-RAHIM, SHARANIZA; KAMSANI, YUHANIZA SHAFINIE; NOOR KHAN, NOR ASHIKIN MOHAMED; RAJIKIN, MOHD HAMIM (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to determine the effects of the tocotrienol-rich fraction (TRF) on the regulations of phosphoinositide 3-kinases (PI3K)/Akt pathways related genes in preimplantation embryos induced by nicotine (Nic). Methods: Twenty-four female BALB/c mice were divided into four groups with Nic and TRF supplementation for 7 consecutive days. Animals were superovulated before mating with fertile males. Plasma malondialdehyde, superoxide dismutase, catalase, and glutathione peroxidase were determined and analyzed accordingly. Embryos with two and eight blastomeres were assessed for gene expression analysis. Results: The levels of endogenous antioxidative enzymes for the group with TRF intervention and TRF only group showed no significant changes when compared to the control group. The level of oxidative stress (OS) biomarkers was also significantly decreased when compared to the Nic-induced group. At 2-cell stage, Pten gene was significantly upregulated while Akt1, GSK3β, and Mapk1 were significantly downregulated almost similar to the baseline (control) in the Nic-induced mice. Intervention with TRF resulted in a significant downregulated of Pten gene followed by a significant upregulation of other genes. The same pattern was shown at the 8-cell stage. Conclusion: This showed that TRF evidently has OS protection capacity and it could be through modulating the PI3K/Akt signaling pathway.